2016
DOI: 10.1016/j.jnucmat.2016.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the oxygen partial pressure and thermodynamic modeling of the U–Nd–O system

Abstract: Fission products greatly impactthe properties of fuel necessitating a thorough understandingof the thermochemical properties of oxide fuels with fission products. However, thermochemical data for the U-Nd-O system is insufficient even though neodymium is a major fission product. As neodymium will likely be present as a solute in UO 2 , this research focuses on the study of (U 1-y Nd y)O 2±x. Experimental measurements and analyses of the oxygen partial pressure (pO 2)-temperature-oxygen to metal ratio (O/M rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The FCC structure is maintained in all cases. At all compositions and annealing temperatures, the system shows only a single fluorite-like phase, which agrees with what is proposed by several authors for hypo-stoichiometric conditions [8,29,[32][33][34][35]. Therefore, the results presented in this work differ from those published by Desgranges et al and Dottavio et al [18], [30], [36] where a miscibility gap was identified: no peak splitting is observed in the samples object of this study and therefore there is no evidence for a phase separation.…”
Section: Ionsupporting
confidence: 91%
See 2 more Smart Citations
“…The FCC structure is maintained in all cases. At all compositions and annealing temperatures, the system shows only a single fluorite-like phase, which agrees with what is proposed by several authors for hypo-stoichiometric conditions [8,29,[32][33][34][35]. Therefore, the results presented in this work differ from those published by Desgranges et al and Dottavio et al [18], [30], [36] where a miscibility gap was identified: no peak splitting is observed in the samples object of this study and therefore there is no evidence for a phase separation.…”
Section: Ionsupporting
confidence: 91%
“…This means that the local distances of the first shell will vary depending if it is U or Nd, which is consistent with the observation of the variation of the k space mentioned earlier in the document. Similar conclusions were seen in [27,35]. Barabash et al argued that the atoms of Nd, which are inserted randomly on the cationic sub lattice, are able to push the surrounding atoms of oxygen out of their regular position, creating a local structural disorder along with the distortion created by the size mismatch between the Nd 3+ , U 4+ and U 5+ cations.…”
Section: Theoretical (%)mentioning
confidence: 53%
See 1 more Smart Citation
“…This force at the thermodynamic equilibrium is proportional to the chemical potential of oxygen gas that is required for attaining a certain degree of hypo- or hyper-stoichiometry. Indeed, a large experimental effort has been invested in studying effects of Ln -doping on the chemical potential of oxygen in equilibrium with a given degree of hypo- or hyper-stoichiometry at a fixed temperature ( Hagemark and Broli, 1967 ; Tetenbaum and Hunt, 1968 ; Javed, 1972 ; Saito, 1974 ; Une and Oguma, 1983a ; Nakamura and Fujino, 1987 ; Lindemer and Sutton, 1988 ; Yoshida et al, 2011 ; Lee et al, 2016a ; McMurray and Silva, 2016 ). These experiments invariably show that the larger the doping, the higher is the chemical potential, or, equivalently, the partial pressure of oxygen, at which a given degree of non-stoichiometry can be attained.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, all condensed phases were assumed to be immiscible as was done for UeGd [34], UeLa [39], UeY [40], and UeNd [41]. A tentative diagram of the UeCe binary is shown in Fig.…”
Section: The Uece Binary Phase Diagrammentioning
confidence: 99%